Takotsubo syndrome outcomes predicted by thyroid hormone signature: insights from cluster analysis of a multicentre registry - Aweimer, Assem; Dietrich, Johannes W.; Santoro, Francesco; Fàbregas, Mireia Camins; Mügge, Andreas; Núñez-Gil, Iván J.; Vazirani, Ravi; Vedia, Oscar; Pätz, Toni; Ragnatela, Ilaria; Arcari, Luca; Volpe, Massimo; et al. (EBioMedicine, 2024)
Background - Recently, abnormal thyroid function was shown to be common in patients with Takotsubo syndrome (TTS), being classified into “endocrine-type” and “stress-type” responses. The aim of this study was to investigate the association between thyroid homeostasis and TTS in a larger international registry. - Methods - In total 288 patients with TTS were enrolled through the GEIST multicentre registry from Germany, Italy and Spain. Thyrotropin (TSH), free T4 (FT4) and free T3 (FT3) concentrations were analysed at admission. Data were collected both retrospectively and prospectively from 2017 onwards. Primary endpoints included in-hospital and all-cause fatality, determined by cluster analysis using an unsupervised machine learning algorithm (k-medoids). - Findings - Three clusters were identified, classifying TTS with low (TSLT), high (TSHT) and normal (TSNT) thyroid output, based on TSH and FT4 levels in relation to the median thyroid’s secretory capacity (SPINA-GT). Although TSH and FT4 concentrations were similar among survivors and non-survivors, these clusters were significantly associated with patient outcomes. In the longitudinal Kaplan-Meier analysis including in- and out-of-hospital survival, the prognosis related to concentrations of TSH, FT4, and FT3 as well as SPINA-GT, deiodinase activity (SPINA-GD) and clusters. Patients in the TSHT cluster and with cardiogenic shock had a lower initial left ventricular ejection fraction (LVEF). - Interpretation - This study suggests that thyroid hormones may impact the evolution and prognosis of TTS. The findings indicate that thyroid-derived biomarkers may help identify high-risk patients and pave the way for novel personalized and preventive therapeutic options. - Funding - This research was not funded by any public, commercial, or not-for-profit agencies.